Subverting Scriptures
IX, 245 p.
Keywords: This collection seeks to fill the interdisciplinary space that addresses when, why, and how writers strategically reference the Bible for subversive or re-evaluative purposes. It explores the specific biblical pieces used this subversion, and why they are used, with reference to many contemporary sources.